Ածանցումը Գորիսի բարբառում - Քումունց, Մհեր; Բաբայան, Արինե (ՀՀ ԳԱԱ ԼԻ հրատ.)
Our study is devoted to the derivation and the examination of suffixes in the Goris dialect. Throughout the study and description of each suffix, we considered it necessary to present relevant examples with each suffix and give their explanations. Studying the suffixes in the Goris dialect, we see that they have given numerous new meanings to words and have their own characteristics. The Goris dialect has its own rich derivation system, through which the dialect vocabulary has been enriched. Производные слова в Горисском диалекте.-Наше исследование посвящено образованию и рассмотре-нию суффиксов в горисском диалекте. В ходе всего исследования и при описании каждого суффикса мы сочли необходимым привести соответствующие примеры и дать пояснения к их особенностям. Изучая суффиксы в горисском диалекте, мы видим, что они придали словам ряд новых значений и обладают особыми особенностями. Горисский диалект имеет богатую словообразовательную систему, благодаря которой обогатился словарный запас диалекта.
Keywords: Բարբառագիտություն